Feministic Islamophobia: Representation of Muslim Women in V.S. Naipaul's Travelogues and Daniel Pipes' History. Issue 4 (2nd October 2021) - Habibullah, Md.
Abstract: When feminism is co-opted to caricature Islam and Muslim men as patriarchal and oppressive to women, it may cause Islamophobia. This interrelation between feminism and Islamophobia can be called 'Feministic Islamophobia'. Such Islamophobia is reflected in V. S. Naipaul's travelogues – "Among the Believers: An Islamic Journey" (1981) and "Beyond Belief: Islamic Excursions among the Converted Peoples" (1998). An advocate of these travelogues Daniel Pipes (1949- ) wrote an Islamic history – In the Path of God: Islam and Political Power (1983) – that, like Naipaulian travelogues, represents feministic Islamophobia. This article argues that the co-opted feminism of both Naipaul's travelogues and Pipes' history causes feministic Islamophobia that is one of the causes of intertextual dynamic between their texts.